Genome-wide identification of growth-regulating factor transcription factor family related to leaf and stem development in alfalfa - Sun, Yue; Li, He; Wu, Jiajing; Zhang, Kangning; Tang, Wei; Cong, Lili; Xie, Hongli; Wang, Zeng-Yu; Chai, Maofeng (Frontiers in Plant Science, 2022)
Growth-regulating factors (GRFs) play crucial roles in plant growth and stress response. To date, there have been no reports of the analysis and identification of the GRF transcription factor family in alfalfa. In this study, we identified 27 GRF family members from alfalfa (Medicago sativa L.) 'Xinjiang Daye', and analyzed their physicochemical properties. Based on phylogenetic analysis, these MsGRFs were divided into five subgroups, each with a similar gene structure and conserved motifs. MsGRFs genes are distributed on 23 chromosomes, and all contain QLQ and WRC conserved domains. The results of the collinearity analysis showed that all MsGRFs are involved in gene duplication, including multiple whole-genome duplication or segmental duplication and a set of tandem duplication. This indicated that large-scale duplication is important for the expansion of the GRF family in alfalfa. Several hormone-related and stress-related cis-acting elements have been found in the promoter regions of MsGRFs. Some MsGRFs were highly expressed in young leaves and stems, and their expression decreased during development. In addition, the leaf size of different varieties were found to vary, and MsGRF1 to 4, MsGRF18 to 20 and MsGRF22 to 23 were differentially expressed in large and small leaf alfalfa varieties, suggesting that they are critical in the regulation of leaf size. The results of this study can benefit further exploration of the regulatory functions of MsGRFs in growth and development, and for identifying candidate genes that control leaf size development.